Effects of Operational Conditions on Exergy Behaviour of Biomass Densification System and Durability of the Densified Biomass - Olaoye, J. O.; Olotu, F. B.; Lasode, O. A.; Duniya, I. P. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Energy resources such as electricity and fuel are used to power biomass densification system for production of solid biofuel, however, energy consumption of the densification equipment has led to high cost of production of the solid biofuel. Meanwhile, energy stored in fuel or the electricity is being used to budget for the work or power requirements during densification of biomaterials which are mostly considered as energy consumption. The energy consumption does not give appropriate recognition to the exact or useful energy from the energy source that is energy output of the system. This study to investigates the effects of operational conditions of a biomass densification system on the exergy behaviour of a biomass densification system. The exergy parameters such as exergy input and exergy output were considered to determine the behaviour of biomass densification system. The conditioned biomass materials at 6%, 10% and 14% moisture contents (MC) were densified at selected applied pressures of 186.56, 211.38, 236.25, 261.17, 286.07 and 310.85 MPa, while each selected pressure was applied at different speeds of 10, 20, 30, 40, 50 mm/min. The exergy parameters obtained were subjected to statistical analysis using IBM SPSS 20.0 to determine the effects of the operational conditions on the exergy behaviour of biomass densification system. The highest mean values of exergy output of 0.3562 J and 0.4033 J were observed at 10 mm/min when pressure of 310.85 MPa was applied using sawdust and huskdust both at 6% MC, respectively to produce one-unit average weight of 12g of biofuel. The least mean values of exergy output of 0.1001 J and 0.1738 J were observed at 50 mm/min when pressure of 186.56 MPa was applied using sawdust and huskdust both at 14% MC respectively. Additionally, densified biomass of high durability was obtained when both sawdust and huskdust were densified at 10% Mc wet basis while the less durable densified biomass was obtained at 6% MC for sawdust and huskdust. Therefore, the operational conditions of biomass densification system such as applied pressure, speed of pressing piston and MC of biomass materials had effects on the exergy input and exergy output as well as the durability of the densified biomass.It was then concluded from this study that the operational conditions of biomass densification system can affect the exergy behavior of the system and the quality of densified biomass.